The Effect of M-Health Utilization with Audiovisual Education Approach on Treatment Adherence Behavior in Tuberculosis Patients - Rivaldo I. Berahim; Herlina Jusuf; Sri Manovita Pateda (Indonesian Journal of Global Health Research, 2025)
In Indonesia, the success rate of TB treatment in 2023 has not yet reached the national target. Treatment of TB aims to cure the patient, prevent death, and prevent drug resistance. However, patients often fail to adhere to treatment due to the lengthy treatment period and side effects of the medication. The utilization of M-Health as a medium for audiovisual education is one of the efforts that can be made to improve treatment adherence behavior. The purpose of this study is to determine the effect of utilizing WhatsApp-based M-Health with an audiovisual education approach on treatment adherence behavior, reviewed from the aspects of knowledge, attitude, and action, in tuberculosis patients. This study uses a Quasi-experimental design with a pre-test and post-test with control group design. The sample in this study consisted of TB patients undergoing Anti-Tuberculosis treatment in North Bolaang Mongondow Regency, with a total of 80 respondents, comprising 40 treatment group respondents and 40 control group respondents. The sample was selected using the purposive sampling technique. The research instrument used was a questionnaire administered to respondents to measure their knowledge, attitudes, and action. Statistical analysis was conducted using Paired t-test, Wilcoxon signed-rank test, and Mann-Whitney test. The results of this study indicated a statistically significant difference in knowledge, attitude, and action scores pre- and post-intervention (p = 0.000). Additionally, the Mann-Whitney test demonstrated a significant difference in knowledge, attitude, and action between the intervention and control groups (p = 0.000). The utilization of M-Health with an audiovisual education approach has a positive impact on improving treatment adherence behavior in terms of knowledge, attitude, and action.